Water quality assessment using the STORET method and formulation of pollution control strategies in the Sangatta River, East Kutai Regency, Indonesia - Sandra, Novita Dwi; Rizal, Samsul; Hamdhani, Hamdhani (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
The Sangatta River, located in East Kutai Regency, East Kalimantan, is a vital water resource that plays a significant role in supporting both local communities and ecosystems. However, the increasing pressure on this river necessitates regular monitoring to assess its water quality status. This study aims to assess and analyze the water quality of the Sangatta River, determine its water quality status, and identify potential measures for controlling water pollution in the river. The research employed the STORET method. Based on this method, the results were as follows: -22 (upstream 1), -34 (upstream 2), -50 (downstream 1), -54 (downstream 2), and -40 (downstream 3). These findings indicate that the Sangatta River is classified as heavily polluted, with an overall score of -40 according to the STORET method. Efforts to control river water pollution should focus on social and institutional aspects, particularly by enhancing community participation in pollution control efforts for the Sangatta River.